Methanolic extract of Teucrium Polium L potentiates the cytotoxic and apoptotic effects of anticancer drugs of vincristine, vinblastine and doxorubicin against a panel of cancerous cell lines - Rajabalian, S. (Experimental Oncology, 2008)
A growing body of evidence indicates that specific phytochemicals can increase an efficacy of cancer chemotherapy. Aim: To evaluate promoting effect of the methanolic extract of Teucrium Polium (Me-TP) on cytotoxic and apoptotic activity of anticancer drugs of vinblastine, vincristine and doxorubicin in vitro. Methods: Skmel-3, Saos-2, SW480, MCF-7, KB, EJ and A431 cell lines were used. Cytotoxicity was determined by MTT assay and colony formation assay. The nature of interactions was analyzed by combination index (CI) method. Apoptotic cells were assessed by DAPI staining. Results: The vincristine/Me-TP, vinblastine/Me-TP and doxorubicin/Me-TP combinations showed a strong synergistic effect in the cell growth inhibition (0.13 < CI < 0.36). Similar results were observed by colony formation assay. Furthermore, the combinations of vincristine/Me-TP and vinblastine/Me-TP resulted in a massive apoptosis (> 80%) compared to effect of individual drugs (0–3%). At the additional experiments, Me-TP reduced marginally to significantly the cytotoxic effects of vincristine and vinblastine toward the human fibroblasts (p < 0.05 to 0.001). Conclusions: The present study suggests that Me-TP has the potential to be an effective and safe chemosensitizer agent for cancer therapy.